2018
DOI: 10.1111/cea.13256
|View full text |Cite
|
Sign up to set email alerts
|

High‐ and low‐dose oral immunotherapy similarly suppress pro‐allergic cytokines and basophil activation in young children

Abstract: Peanut OIT leads to decreases in pro-allergic cytokines, including IL-5, IL-13, and IL-9 and decreased basophil activation. No differences in T cell or basophil responses were found between subjects on low or high-dose maintenance OIT, which has implications for clinical dosing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…Levels of CD203c expression in basophils after anti-IgE, IL-3, or peanut stimulation were also similar between the 3 treatment arms at baseline ( Fig E1, C). Consistent with previous OIT studies of peanut allergy, 7,18,[25][26][27] our OIT protocol significantly decreased peanut-induced %CD63 high basophils as early as week 12 of the OIT build-up phase (Fig 1, A). Upregulation of CD63 in basophils was suppressed during the OIT maintenance phase from weeks 52 to 104.…”
Section: Peanut Oit Suppresses Basophil Activation and Reduces Peanutsupporting
confidence: 90%
See 1 more Smart Citation
“…Levels of CD203c expression in basophils after anti-IgE, IL-3, or peanut stimulation were also similar between the 3 treatment arms at baseline ( Fig E1, C). Consistent with previous OIT studies of peanut allergy, 7,18,[25][26][27] our OIT protocol significantly decreased peanut-induced %CD63 high basophils as early as week 12 of the OIT build-up phase (Fig 1, A). Upregulation of CD63 in basophils was suppressed during the OIT maintenance phase from weeks 52 to 104.…”
Section: Peanut Oit Suppresses Basophil Activation and Reduces Peanutsupporting
confidence: 90%
“…21,22 Some studies have suggested that BATs are more reliable than skin prick tests and sIgE levels in differentiating food allergy from tolerance in children. 32,34 Although suppression of basophil activation by immunotherapy has been demonstrated in food allergy to egg, 37 milk, 38 and peanut, 7,8,18,[25][26][27]39,40 only a few studies have examined the association of basophil activation with treatment outcomes. 18,26,27,37,40,41 Our analysis of BAT results obtained for more than 2 years in the POISED study shows that basophil activation remains suppressed even after 13 weeks off active OIT, and that sustained protection is associated with lower levels of basophil activation by peanut before, during, and after OIT.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the SU rate did not differ significantly by peanut OIT dose (ITT: 71% high dose, 85% low dose). Mechanistic studies supported this finding with decreases in basophil reactivity, peanut SPT, and pn‐sIgE, and T H 2 cytokines (IL‐5, IL‐13, IL‐9) demonstrated across all subjects but with no difference between high‐ and low‐dose OIT subjects . Safety, on the other hand, did appear to favor the lower dose.…”
Section: Peanut Oitmentioning
confidence: 69%
“…We considered that low dose and high dose did not differ in the effect of rush OIT for severe milk allergy. Kulis et al [8] reported no significant differences in proallergic cytokines, including IL-5, IL-13, and IL-9, T cells, or basophils between low-and high-dose peanut OIT. Yanagida et al [5] reported that the effect of increasing the threshold was observed by continuing a maximum of 3 mL of milk OIT in children severely allergic to milk.…”
Section: Discussion/conclusionmentioning
confidence: 98%